1986
DOI: 10.1038/bjc.1986.84
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sample source and cell concentration on the in vitro chemosensitivity of haematological tumours

Abstract: Summary The Differential Staining Cytotoxicity (DiSC) assay has been used to study the effects of sample source and cell concentration on the in vitro chemosensitivity of haematological malignancies.The chemosensitivity of blood and bone marrow samples was significantly associated (P<0.001) in 12 cases where both were tested simultaneously. In 8 of the cases, where the in vitro result could be compared with clinical response, the in vitro and in vivo chemosensitivity was in agreement in 7, for both blood and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The correlation for all 106 paired BM and PB LC50 comparisons was very good, with most pairs close to the ideal line x = y (Figure 3). Our findings agree with those of Bird et al (1986), who reported a significant association in sensitivity to a maximum of six drugs of leukaemic BM and PB cells from 12 patients. The same was found by Sargent and Taylor (1989) and Spiro et al (1981a), in single cases.…”
Section: Reagentssupporting
confidence: 80%
“…The correlation for all 106 paired BM and PB LC50 comparisons was very good, with most pairs close to the ideal line x = y (Figure 3). Our findings agree with those of Bird et al (1986), who reported a significant association in sensitivity to a maximum of six drugs of leukaemic BM and PB cells from 12 patients. The same was found by Sargent and Taylor (1989) and Spiro et al (1981a), in single cases.…”
Section: Reagentssupporting
confidence: 80%
“…Leukaemic blasts from bone marrow and peripheral blood also behave similarly in the DiSC assay (Bird et al, 1986).…”
Section: Appraisal Of Methodsmentioning
confidence: 95%
“…We have had good success whether measured by the proportion of tests that give successful results (up to 95%; Bird et al, 1986a) or the correlation of assay results with patient response (overall 86% true positive and true negative correlations; Bosanquet et al, 1983;Bird et al, 1985Bird et al, , 1986bBird et al, , 1988.…”
Section: Introductionmentioning
confidence: 99%